2014
DOI: 10.4103/0974-2727.129084
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Blood Culture Techniques in the Diagnosis of Human Brucellosis

Abstract: Background:Isolation of Brucella is the gold standard in the laboratory diagnosis of brucellosis. As Brucella is intracellular and the number of circulating bacteria is usually low, removal/dilution of antibacterial substances, concentration of bacteria and optimal culture conditions may enhance the rate of isolation.Aims and Objectives:The objective of the following study was to compare the lysis concentration (LC), clot culture and conventional Castaneda blood culture techniques for the isolation rate and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…However, these methods are time-consuming and require specialized technicians. Of note, it may require weeks to obtain a correct diagnosis of some pathogens from samples of mucosa, skin, or blood (Benes et al, 1996). Unfortunately, a few days may be sufficient to significantly worsen the clinical status of the patient before receiving appropriate treatment.…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%
“…However, these methods are time-consuming and require specialized technicians. Of note, it may require weeks to obtain a correct diagnosis of some pathogens from samples of mucosa, skin, or blood (Benes et al, 1996). Unfortunately, a few days may be sufficient to significantly worsen the clinical status of the patient before receiving appropriate treatment.…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%
“…[3,11,12] The most commonly used serological tests are the Rose Bengal (RB) plate test and the standard serum tube agglutination (STA) test. [3,11] However, these commonly used tests cannot detect so-called 'incomplete/ blocking antibodies' that prevent agglutination, especially in chronic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 27 patients with chronic disease, the detection rates were 3.3% (n=9) for the Castañeda flask and 74.1% (n=20) for the lysis centrifugation method (P=0.087), and the timeto-detection was 7.2±2.6 and 2.7±1.4 days, respectively (P=0.001). In a more recent study, the lysis centrifugation recovered B. melitensis in 73 (43.1%) of 169 serologically-confirmed human cases, compared to 42 (24.8%) detected by the blood clot culture and 59 (34.9%) by the Castañeda technique, and the detection time was significantly shorter [29].…”
Section: Lysis Centrifugation: In-house and Commercial Methodsmentioning
confidence: 99%
“…In a comparative study of 169 serologically confirmed patients, Mangalgi and Sajjan reported a detection rate of 34.9% for the clot culture, 24.8% for the Castañeda flask, and 43.1% for the lysis concentration method; the mean±SD recovery times were 5.8±1.4, 9.6±1.7, and 4.1±0.9 days, respectively [29]. In a second study by the same research group, blood clot cultures were clearly superior to conventional broth cultures of whole blood for isolating brucellae, increasing the yield by >20% and shortening the time-to-positivity from an average of 8.2 days to 3.1 days [59].…”
Section: Blood Clot Culturesmentioning
confidence: 99%
See 1 more Smart Citation